Soviet Economic Policy in Middle Volga Region during Early 1920s - I. A. Gataullina (Научный диалог, 2025)
This article examines the implementation of the New Economic Policy (NEP) in the Tatar Republic, Ulyanovsk, Samara, and Saratov provinces. The institutional principles governing the organization of the internal market, developed within the framework of Lenin’s project, are identified as the foundation of economic activity. The results of a comparative analysis of the regional network are presented. It is established that the rapid growth of trade was driven by the dynamics of absolute indicators in the private sector and the strengthening positions of state and cooperative sectors. It is emphasized that while there was a shift towards state entities in provincial trade turn-over, a balanced ratio of trading competitors with an advantage for private capital was observed in the Tatar Republic. The study argues that the revival of market conditions, influenced by prior experience, initiated an evolutionary direction for the policies being implemented. It is shown that regulation reflected a measured approach by authorities towards private competition and their desire to critically assess their actions regarding cooperation. However, instances of incompetence and simplified solutions to pressing issues suggest that the legitimization of arbitrary state power to interfere in the recovery process is merely a matter of time. The author concludes that the counterbalance to the destructive force of class hatred can only be found in the constructive potential of social partnership, which builds an economy based on compromise.